Associations of eldercare and competing demands with health and work outcomes among manufacturing workers. Issue 5 (19th October 2016) - Dugan, Alicia G.; Fortinsky, Richard H.; Barnes-Farrell, Janet L.; Kenny, Anne M.; Robison, Julie T.; Warren, Nicholas; Cherniack, Martin G.
ABSTRACT: Employees juggling eldercare and work report work–family conflicts and poor health-related outcomes, but little is known about eldercare demands (ECDs) in the context of competing demands in the manufacturing workforce. This study determines how ECDs vary by age, gender, income, and job category, and how ECDs and competing demands are associated with health-related and work-related outcomes, among manufacturing workers. Employees from six manufacturing companies completed questionnaires. ECDs were defined as providing assistance to an adult aged 65 and older due to disability or chronic illness; those with ECDs were asked how many care-hours per week and whether assistance included personal care. Workers over age 45 were more likely than younger workers to report ECDs. After adjusting for competing demands and socio-demographic characteristics, ECDs were associated with greater depressive symptoms and family-to-work conflict (FWC), providing 5 or more hours of eldercare weekly was associated with greater depressive symptoms, and providing personal care was associated with greater FWC.